2022
DOI: 10.1101/2022.04.05.487153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Architecture of the chikungunya virus replication organelle

Abstract: Alphaviruses are mosquito-borne viruses that cause serious disease in humans and other mammals. Along with its mosquito vector, the alphavirus chikungunya virus (CHIKV) has spread explosively in the last 20 years, and there is no approved treatment for chikungunya fever. On the plasma membrane of the infected cell, CHIKV generates dedicated organelles for viral RNA replication, so-called spherules. Whereas structures exist for several viral proteins that make up the spherule, the architecture of the full organ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 50 publications
3
10
1
Order By: Relevance
“…The simplest model explaining this observation is that the[-] RNA varies in the extent to which it is double stranded in different viral RCs and it is this that correlates with both cleavage and the suppression of replication. Certainly, recent electron cryotomography studies on CHIKV replication spherules would support the notion that this viruses [-] RNA is sequestered away in a double stranded state, consistent with the lack of cleavage we observed in our studies(Laurent et al 2022;Tan et al 2022). Interestingly, these same studies suggest that the viral helicase nsp3 is either not associated with the replicase proteins found at the neck of the spherule, or if it is then this association in on the cytoplasmic rather than the lumen face.…”
supporting
confidence: 91%
“…The simplest model explaining this observation is that the[-] RNA varies in the extent to which it is double stranded in different viral RCs and it is this that correlates with both cleavage and the suppression of replication. Certainly, recent electron cryotomography studies on CHIKV replication spherules would support the notion that this viruses [-] RNA is sequestered away in a double stranded state, consistent with the lack of cleavage we observed in our studies(Laurent et al 2022;Tan et al 2022). Interestingly, these same studies suggest that the viral helicase nsp3 is either not associated with the replicase proteins found at the neck of the spherule, or if it is then this association in on the cytoplasmic rather than the lumen face.…”
supporting
confidence: 91%
“…So far, we investigated the conformation of sections of the dsRNA within spherules, but did not yet study its overall packaging. Using the volume measurements we previously performed for individual spherules (14), and assuming dsRNA to have a diameter of 24 Å (excluding its hydration shell), we found that the traced amount of dsRNA occupied 7.6 ± 0.9 % of the spherule lumen (Fig. 2A).…”
Section: The Rna Occupies the Spherule Lumen Uniformlymentioning
confidence: 90%
“…The total resolved amount of dsRNA in the five classes reflects 52% of the genome length. The remaining 48% of genome might be present in more variable dsRNA conformations that were averaged out, or as single-stranded RNA (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations